2009
DOI: 10.1097/mpg.0b013e31818b0ac7
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy in the Evaluation of Patients With Unexplained Growth Failure

Abstract: In our study, 4 of the 7 older children and adolescents with unexplained growth failure and normal small bowel series were found to have Crohn disease involving the small intestine. In addition, we were able to show the improvement on the mean z score for weight after treatment of small bowel Crohn disease was instituted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…On the other hand, a previous study showed the indication rate of suspected CD as 7.8% in adult patients (Rondonotti, 2010). Because a known CD increases a risk of capsule retention possibly caused by an intestinal stricture (Cheifetz, 2006;Moy, 2009;Atay, 2009), it is recommended to avoid the use of CE for the evaluation of known CD in both adult and children. In regard to the diagnostic accuracy, the previous pediatric study elucidated that CE was a more effective diagnostic tool in established CD patients compared with small-bowel radiography, CTE, and push enteroscopy (Thomson, 2007).…”
Section: Chron's Disease or Inflammatory Bowel Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, a previous study showed the indication rate of suspected CD as 7.8% in adult patients (Rondonotti, 2010). Because a known CD increases a risk of capsule retention possibly caused by an intestinal stricture (Cheifetz, 2006;Moy, 2009;Atay, 2009), it is recommended to avoid the use of CE for the evaluation of known CD in both adult and children. In regard to the diagnostic accuracy, the previous pediatric study elucidated that CE was a more effective diagnostic tool in established CD patients compared with small-bowel radiography, CTE, and push enteroscopy (Thomson, 2007).…”
Section: Chron's Disease or Inflammatory Bowel Diseasementioning
confidence: 99%
“…On the other hand, evaluation of entire small intestine is sometimes not completed because of prolonged gastric emptying and limited battery life (< 8h). In pediatric patients, completion rate of CE in the entire small intestine varies from 69 -89 % (Tokuhara, 2010;Guilhon de Araujo Sant'Anna, 2005;Atay, 2009;de'Angelis, 2007;Moy, 2009;Postgate, 2009). In order to improve the completion rate, mosapride citrate or laxatives are one of candidate to increase the ability to observe the entire small intestine, but there is no systematic study in regard to the use of mosapride or laxatives as a preparation drug for CE study in pediatric patients.…”
Section: Preparations For Cementioning
confidence: 99%
See 2 more Smart Citations
“…In the pediatric IBD patient group, WCE may be valuable in evaluating children with growth retardation when traditional studies have been unrevealing and in children with UC and IBDU may be used to reclassify the disease [38,39] . In a recent study, 4 of the 7 (57%) older children and adolescents with unexplained growth failure and normal SB series were found to have CD involving the small intestine [38] .…”
Section: Wireless Capsule Endoscopymentioning
confidence: 99%